Stilistika v svete tipov rečevoj kulʹtury - Sirotinina, Ol’ga O. (Stylistyka, 2021)
The рарег is fo^sed оп different aspects of the соггеЫюп between stylisties а^ types of speech сиЙиге. It is arguedt апу kind of stylisties studies опіу the highest type of speech culture common to people who have a perfect command of all language varieties. In other words, stylistics always deals exclusively with the accepted model of good speech. The first part of the paper concentrates on the essence of three branches of stylistics: functional stylistics, literary stylistics, and practical stylistics. Functional stylistics studies functional differentiation of standard language (the Russian equivalent of the English term standard language is numepamypmrn язык). Practical stylistics is aimed at choosing the best synonym. Literary stylistics analyses fictional texts whose authors make a maximum use of language resources. Only people of the fully functional type of speech culture can cope with the above-mentioned tasks. The second part of the paper is devoted to a study of the peculiarities of speech culture markers manifestation in different language varieties. A close analysis of extensive factual data has led the author to the conclusion that speech culture markers are most active in public and fiction discourse and least active in standardized documents and casual everyday conversation.